FEʼLLI FRAZEOLOGIK BIRLIKLARNING SINTAKTIK - SEMANTIK XUSUSIYATLARI (INGLIZ VA OʻZBEK TILLARI MISOLIDA) - Xolikulova Aziza Sheralievna, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article is devoted to the study of syntactic-semantic properties of verb phraseological units in English and Uzbek. The article analyzes aspects of verb phraseological units such as structure, meaning properties, and applicability. According to the results of the study, a number of similar and different aspects were identified between the verb phraseological units in English and Uzbek.